Persepsi Masyarakat Terhadap Kewajiban membayar Pajak Bumi dan Bangunan di Kecamatan Slawi Kabupaten Tegal - Subhan Juniar Adithama; yuwanto .; lusia astrika (Journal of Politic and Government Studies, 2016)
ABSTRACTThis study was undertaken to explain how the public perception of the obligation topay the Property Tax (PBB) in Slawi Sub-District. The aims of this study was to describe thepublic perception of the obligation to pay the Property Tax (PBB) in Slawi Sub-district, andto setermine the factors that influence the formation of public perceptions of the obligation topay Property Tax. This research uses quantitative-descriptive type with survey method,namely the taking of samples from a population and using a questionnaire as a datacollection tool By doing so, it produces to explain the variety of conditions where is theresearch was founded. Based on those founding then this research describe character/pictureof the condition, situation, or variables. Population of the research is the Slawi Sub-districtcommunity, the sample taken from the entire village using Frank Lynch with a total of 100samples. From the data processing research indicates that the most of respondent knew aboutwhat is Property Tax (PBB). Slawi Sub-districtawareness in the Property Tax to pay highenough it can be seen from the level of public education began to improve. Socializationprovided by the local government has also been quite good but not yet maximum, as well asthe Slawi Sub-district community agree that DPPKAD has prepared an integrated service